Subunit Reconstruction of Massive Heel Wounds Using Medial Plantar Artery and Chimeric Thoracodorsal Artery Perforator Flaps - Emmanuel Nageeb, MD; Manasa Pavuloori, BS; Jason DJohn, MD; John M. Felder, MD (Plastic and Reconstructive Surgery, Global Open)
Summary:. Heel wounds in patients with diabetes and peripheral vascular disease present significant reconstructive challenges due to their location on a weight-bearing surface and the high risk of delayed wound healing. These wounds require durable coverage that can withstand mechanical stress. The medial plantar flap is the ideal reconstruction for glabrous defects, but may be limited by insufficient tissue availability and donor site morbidity, which is more significant in patients with compromised healing potential. A 64-year-old man with uncontrolled type 2 diabetes presented with a severe right heel wound, complicated by osteomyelitis and extensive tissue loss. Surgical treatment included excisional debridement, partial calcaneal resection, and reconstruction with a pedicled medial plantar artery flap (MPAF) for the weight-bearing heel subunit. A chimeric thoracodorsal artery perforator (TDAP) flap was used to provide additional coverage for the posterior subunit of the wound and the MPAF donor site. Postoperatively, the patient had no flap-related complications. Two minor areas of wound dehiscence were treated with re-excision and closure. At the final follow-up, the patient demonstrated full wound healing and resumed ambulation without further complications. The combined use of MPAF and TDAP flaps provides immediate, durable coverage for wounds encompassing multiple heel subunits, as well as immediate closure of the high-risk MPAF donor site. The thick back skin of the TDAP is ideal for durability with weight-bearing. This dual-flap approach offers a promising solution for challenging reconstructions in weight-bearing areas and may help prevent complications such as donor site wound breakdown.